Research on Legal Guarantee for Green Development of Fisheries in Liaoning Province - WU Yifan; LIN Yan (Haiyang Kaifa yu guanli)
Agriculture is the foundation of the country, and fishery is a key link in the process of agricultural development. Conducting relevant legal guarantee research on the green development of Liaoning's fishery is important for the implementation of General Secretary Xi Jinping's key conclusion that "lucid waters and lush mountains are invaluable assets." It has practical significance and is consistent with the spiritual axis of socialist ecological civilization. It aims to prevent the fishery economic development in Liaoning Province from breaking through the bottom line of the ecological environment, in line with intergenerational justice, making contributions to the present and benefiting the future. In order to achieve sustainable development of fishery, we must pay attention to the establishment and improvement of green development concepts and legal guarantee mechanisms. This article analyzes the connotation, significance and legal protection status of fishery green development in Liaoning Province from the perspective of the connotation, significance and legal protection status of fishery green development in Liaoning Province. The problems existing in the process of fishery green development in Liaoning include the lagging legislation of fishery green development, the absence of supporting implementation details for fishery green development and the imperfect fishery supervision system. It also gives solutions to strengthen the systematic special legislation for green fisheries, improve the supporting implementation rules of fishery laws, and improve the fishery supervision system. It is hoped that by exploring the legal protection issues existing in the green development of Liaoning's fishery, effective policy suggestions and decision-making support can be provided.